KEEFEKTIFAN CENDAWAN Beauveria bassiana Vuill TERHADAP MORTALITAS KEPIK HIJAU Nezara viridula L. PADA STADIA NIMFA DAN IMAGO - Hasnah Hasnah; Susanna Susanna; Husin Sably (Jurnal Floratek, 2012)
The objectives of the study was to obtain an effective concentration of B. bassiana to control pests of N. Viridula.  Experiment was performed at Laboratory of Pest, Agriculture Faculty, Syiah Kuala University Darussalam, Banda Aceh. The experiment used a  faktorial completely randomized design (CRD).  Factors evaluated were (1) concentration of B. bassiana consisting of three levels: 2 gL-1 distilled water, 4 gL-1 distilled water, and 6 gL-1 distilled water, and (2) stadia of N. viridula consisting of 2 levels: third instar nymphs and imago. Variable observed were incubation period, mortality of N. viridula, time of death, and percentage of feeding inhibition. The results showed that concentration of B. bassiana and stadia of N. viridula had no effect on incubation period of fungus B. bassiana. Concentration of B. bassiana affected mortality and time of death of nymph and imago N. viridula. Concentration of fungus B. bassiana affected percentage of feeding inhibition. In general, fungus B. bassiana had a high potential on controlling insect N. viridula.